The psychological dimensions of Antonym in Arabic rhetoric - Razhan Abdulmutalib, Aya; Mulla Aziz , Salih (Zanco Journal of Human Sciences, 2023)
The Antinomy style within the Arabic rhetoric is represented in two of the Embellishments, namely the Antithesis (Tebaq) and Oxymoron (Muqabala), which are among the most prominent syntagmatic Embellishments that it is difficult for any creative text to be void of. This research aims to reveal an important side of the antinomy style, which is the psychological side. This style has many psychological dimensions, which are the result of its semantic embellishment of speech first and verbal in the second place. In studying these dimensions, the research depends on the analytical method, by shedding light on the references of the ancients and modernists eloquent and critics, as well as to the references of scholars of literary psychology field to this style's psychological dimensions, and then analyzing and commenting on these references and applying them to evidences from the Holy Qur’an and the Prophet’s Hadiths, ancient and modern poetic verses, and prose texts. The nature of the scientific material required to distribute it into an introduction, two pillars, and a conclusion. The introduction elaborates generally on the importance of psychological dimensions in linguistic expression. As for the first pillar, it examines the concept of antinomy in Arabic rhetoric and the resulting terminology, while the second pillar deals with the psychological dimensions of antinomy through the ancient and modern rhetoricians' texts, using the analysis of evidences of multiple visions that support the dimensionns referred to. The conclusion follows the second pillar to summarize the main findings of the research.